Edisi 2 Vol 2 September 2024 HALAL CERTIFICATION AS THE DEVELOPMENT AND PROTECTION OF INAGIRI GAPLEK BREAD UMKM IN WONOGIRI REGENCY - Amirudin, Choirul (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2024)
This study aims to determine the impact of halal certification on the development of business and consumer protection efforts in Indonesia, which is predominantly Muslim. This research is a field research with a qualitative approach. Data collection techniques are interviews, observations, and literature studies. The results of this study show that halal certification is an important part in improving and developing business products because it increases public interest and trust. This Inagiri Gaplek Bread product is a food product that comes from halal food ingredients. Therefore, this product can get a halal certificate as a guarantee of product halalness. The management of this halal certification is easy. Business owners can submit an application to BPJPH which will eventually issue a halal certificate if the product submitted meets the requirements. Halal certification itself is also part of consumer protection efforts considering that the majority of the population in Indonesia is Muslim.